(untitled) (Research, Society and Development, 2020)
An increasing number of people have motor disabilities in the upper limbs and face functional deficiencies, depending on others to perform their routine activities. Motor rehabilitation is characterized by a daily routine of commuting to the clinics, repetitive physical exercises and a slow process of functional recovery, which makes treatment time-consuming, leading the patient to a lack of commitment and abandonment of treatment. In this context, gametherapy solutions have been used for motor rehabilitation, in which interactive scenarios of serious games are used to enhance the humanization of treatment and the patient’s experience during the execution of exercises to recover motor functions. This paper aims to present a serious smart game for motor rehabilitation of upper limbs, which uses computer vision and machine learning models integrated with technologies with wide social insertion, such as cameras built into smartphones, laptops or integrated into TVs. For the implementation of the serious game, the web programming languages, HTML, CSS and JavaScript were used, so incorporating the TensorFlow library and the PoseNet package to control the patient’s movements in the game scenarios. The serious game developed contributes to make gametherapy a present and viable technique in rehabilitation clinics and home environments, since its insertion does not depend on costs associated with technology or infrastructure adaptations in the environment.